Language impairment in Alzheimer's disease and benefits of acetylcholinesterase inhibitors - Ferris SH (Dove Medical Press, 2013)
Steven H Ferris,1 Martin Farlow21Alzheimer's Disease Center, Comprehensive Center on Brain Aging, New York University Langone Medical Center, New York, NY, 2Department of Neurology, Indiana University School of Medicine, Indianapolis, IN, USAAbstract: Alzheimer's disease is characterized by progressively worsening deficits in several cognitive domains, including language. Language impairment in Alzheimer's disease primarily occurs because of decline in semantic and pragmatic levels of language processing. Given the centrality of language to cognitive function, a number of language-specific scales have been developed to assess language deficits throughout progression of the disease and to evaluate the effects of pharmacotherapy on language function. Trials of acetylcholinesterase inhibitors, used for the treatment of clinical symptoms of Alzheimer's disease, have generally focused on overall cognitive effects. However, in the current report, we review data indicating specific beneficial effects of acetylcholinesterase inhibitors on language abilities in patients with Alzheimer’s disease, with a particular focus on outcomes among patients in the moderate and severe disease stages, during which communication is at risk and preservation is particularly important.Keywords: Alzheimer's disease, donepezil, cognition, language, communication, clinical trials